An Agrarian Portrait of HIV - Starling, Summer (Consilience, 2010)
INTRODUCTION [June – August 2008; Arusha, Tanzania; Global Service Corps] An often-unnoticed face of HIV in Tanzania is distinctly agrarian. For farming communities in the Arusha area of Tanzania, the connection between food security and HIV is hard to ignore. About 8 out of 100 people in Tanzania are living with the virus. Livelihoods claimed by the HIV epidemic are increasingly young men and women whose families depend on their labor on family-run gardens and farms. A trend toward young people migrating from their rural communities for life in urban centers has been well documented in the last ten years. This trend, combined with HIV infection rates among the young, have a crippling effect on food security in the isolated hills outside Arusha. Whole communities struggle with drops in local food production, loss of market opportunities, and high imported food costs. Women comprise the majority of Tanzanian food producers in rural settings – roughly 90% of women in Arusha district engage in subsistence farming and market activities every day. As the HIV epidemic reaches more and more rural areas, women bear newer roles as farmers, breadwinners, and caretakers to those family or community members with HIV. Global Service Corps (GSC) is a San Francisco-based non-profit that facilitates HIV education workshops and bio-intensive agriculture trainings for people in the Arusha area, making the critical connection between HIV prevention and sustainable farming. Trainings stress a multi-generational, family-centered approach to HIV prevention, and include discussions around sexual decision-making, negotiation, and condom use. Most recently, GSC has launched HIV-prevention day camps for secondary school students to help them stay HIV-free. Bio-intensive agriculture (BIA) trainings instruct on sack-gardening, crop rotation, companion planting, and other labor-saving farming techniques. These trainings also emphasize family nutrition and sustained crop yield. Numbers of people in the Arusha community receiving both BIA and HIV trainings are on the rise. Embracing an ecological perspective in the fight against HIV and food insecurity, Global Service Corps’ operations set a sustainable example for integrating disciplines on the ground for improved quality of life.